Recto-sigmoid polypectomy by a handmade snare: Experience of 24 children with bleeding per rectum - Manoj Saha (Wolters Kluwer Medknow Publications, 2014)
A handmade snare is designed from easily available materials to treat bleeding per rectum in children due to rectosigmoid polyps. A total of 29 polypectomies were done in 24 patients. It is simple, effective, safe and economic.